Optimization of the Kendal Polres Samapta Unit to Prevent the Crime of Theft with Weight in the Maintenance of Kamtibmas - Yudhansyah, Hafidz Ikhwani (Advances in Police Science Research Journal, 2024)
The main operational functions of the National Police are maintaining public security and order, law enforcement, protecting serving and protecting the community (kantibmas). This function is specifically a samapta function which means samapta preparedness by using preventive measures or 3 prevention against kamtibmas disturbances by guarding and guarding or patrolling. The main targets of the samapta unit are to provide protection, protection, and services to the community when it is suspected that there is a violation of the law, carry out early stage repressive actions and disturbances of kamtibmas, carry out limited law enforcement such as tipiring and local law enforcement, empower animal support in police operational tasks and carry out Search and Rescue (SAR). However, at the location where this thesis research was carried out, namely in the jurisdiction of the Kendal Police Unit, it was known that the Samapta Unit Patrol Unit had not been optimal in carrying out its duties in accordance with its main function, which was to create harkamtibmas. There is a need for optimization efforts by the Kendal Police patrol unit in carrying out its duties to improve harkamtibmas, especially by preventing theft with aggravation. Therefore, this study analyzes the implementation of patrols and efforts to optimize the Kendal Police samapta unit.